Programmable Imaging Amplification via Nanoparticle‐Initiated DNA Polymerization. Issue 23 (1st July 2013) - Chen, Niancao; Li, Shihui; Battig, Mark R.; Wang, Yong
<x xml:space="preserve">Abstract</x> DNA growth on nanoparticles: Nanoparticle‐mediated molecular recognition and DNA polymerization are integrated for extracellular matrix (ECM) imaging via programmable signal amplification. By using DNA monomers labeled with identical or different imaging reagents, it is promising to achieve single‐ or multiple‐modality imaging of the ECM. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>